Gender, property and household in provincial English parish government, c. 1540-1660 - Blackwood, A (2022)
The political structure of early modern England was, definitively, patriarchal. And yet, women wielded direct authority on the local level in the sixteenth and seventeenth centuries at a scale not seen in the periods before or after. While historians have long recognised that early modern parishes occasionally elected female officers, this thesis is the first full-length study of female office-holding in the rural parish. As such, it reveals that we have underestimated the frequency of female nomination to parish office throughout this period, requiring a reevaluation of current historical knowledge on custom, state formation, gender relations and the nature of parish government.